ALTERATION IN BLOOD BIOCHEMICAL PROFILE IN PREGNANT AND NON-PREGNANT CROSSBRED COWS FOLLOWING EXOGENOUS SUPPLEMENTATION OF GNRH, HCG AND PROGESTERONE RELEASING INTRAVAGINAL DEVICES. - N K G, PANDEY; GUPTA, H P; PRASAD, SHIV; SHEETAL, S K (The Indian Journal of Animal Reproduction, 2023)
The present study was designed to evaluate the effect of GnRH, hCG, Progesterone impregnateddevice on blood biochemical profile in crossbred cows. Repeat breeding crossbred cows (n=32), lactating and negative to white side test were randomly divided into four groups; Group-1 (Control, n=8), Group-2(GnRH @ 10μg i.m, n=8), Group-3 (hCG@1500 IU i.m., n=8), Group-4(Progesterone impregnated device @958 mg, =8). All the treatments were given on 5th day post breeding and in group-4 intravaginally implanted device was withdrawn on 9th day of estrous cycle. Blood samples were collected on day 0, 5, 10, 15, and day 20 of estrous cycle and plasma was separated for biochemical estimation like plasma glucose, cholesterol, total protein, albumin and globulin. There were significantly higher plasma glucose and cholesterol level in pregnant animalsas compared to non-pregnant animals of all groups. Plasma glucose level had significantly increased between day O and day 5 of estrous cycle compared to control group of pregnant animals. There was no significant difference found in plasma cholesterol, total protein and globulin level in all the groups on day 0, 5, 10, 15 and of day 20th of estrous cycle. There was significantly (P
Keywords: Blood biochemical profile; Crossbred cow; Pregnant; Non-pregnant